Rationales of Verse: Poe and Other Critics - Barragão, Fernando Pedro Cleto Rodrigues (2012)
“The Rationale of Verse” is probably among the less widely known theoretic/critical essays by Edgar Allan Poe. Nevertheless, it is a text whose rediscovery matters due to the pertinence of most of Poe’s conceptions regarding topics such as prosody and the correct scansion of a poem (if there is such a thing). Poe’s essay is also surprising because of the author’s proposal of a new method for scanning verse based on a musical notation. In this context, other authors such as Gerard Manley Hopkins and Ezra Pound are mentioned as theorists and critics with ideas converging with Poe’s. On a negative note, Poe’s fail to recognize distinctive features of non-English prosodies is exposed with the help of Mikhail Gasparov’s investigations.